Ultrasound-guided quadratus lumborum block verses transversus abdominis plane block for post-operative analgesia in patients undergoing total abdominal hysterectomy: A prospective observational study - Malla, Mohammad Sadiq; Ashraf, Sameena; Najib, Rayees; Hakeem, Abdul (Asian Journal of Medical Sciences, 2021)
Background: Total abdominal hysterectomy (TAH) is a major surgical procedure associated with significant post-operative pain and discomfort. Ultrasound-guided (USG) quadratus lumborum (QL) and transversus abdominis plane (TAP) block are regional analgesic techniques that have role in post-operative pain management after TAH. Aims and Objectives: This study aims to compare quality of post-operative analgesia and analgesic consumption in USG-guided QL block and TAP block in patients undergoing TAH under spinal anesthesia. Materials and Methods: Hundred patients scheduled for TAH were observed over a period of 2 years. The patients who had received either TAP block or QL block were assigned in two groups. Patients who received TAP block after spinal anesthesia were labeled as Group A and patients who received QL block after spinal anesthesia were labeled as Group B. Postoperatively, VAS score, rescue analgesia, analgesic consumption, and hemodynamic parameters were observed at 0, 1, 3 6, 9, 12, 18, 24, and 48 h. Statistical Analysis: Student’s independent t-test was employed for comparing continuous variables. Chi-square test or Fisher’s exact test, whichever appropriate, was applied for comparing categorical variables. P<0.05 was considered statistically significant. Results: Time for rescue analgesic requirement was higher in the Group B than the Group A (mean±SD: 16.5±3.096 h vs. 8.5±1.998 h) (P<0.001). Group B had significantly less analgesic demand (P<0.001) at 12, 24, and 48 h postoperatively. The VAS at rest and movement was significantly reduced in Group B at all times. Hemodynamic parameters and post-operative side effects between two groups remained insignificant. Conclusion: USG-guided quadratus lumber block provided prolonged analgesia as compared to TAP block in patients undergoing TAH after spinal anesthesia. USG-guided quadratus lumber block provides better multimodal post-operative analgesia relief in patients.